Fluctuations of Mineral Ions in Saline Soils and Halophytic Grass Aeluropus Lagopoides L. - Joshi, A J; Bhoite, A S (Annals of Arid Zone, 2016)
Seasonal variations in mineral ion content of saline habitat and leaves, stems and roots of halophytic grass, Aeluropus lagopoides, growing on western coast of India were studied. The salinity (EC 1:2) of soils varied between 10.5 to 34 2 dS m-1 and it reached to maximum during dry period. The Na+ and Cl- ions were the principle constituents of soil salinity and plant tissues but the Cl- content was more than Na+ in both the cases. Mg2+ exceeded the amounts of Ca2+, and K+ occurred in low concentrations in soils and plants.